Efficacy of lemon albedo as fat replacer for development of ultra‐low‐fat chicken patties. Issue 7 (21st May 2021) - Chappalwar, Anita M.; Pathak, Vikas; Goswami, Meena; Verma, Arun Kumar; Rajkumar, Vincent
Abstract: The study was carried out to develop ultra‐low‐fat chicken patties with incorporation of lemon albedo powder. Chicken patties were developed by incorporating lemon albedo powder as fat replacer at 1.0%, 2.05, 3.0% level to replace 50% vegetable oil in formulation. Emulsion and product pH, emulsion stability, fat and cholesterol decreased significantly ( p  < .05), however cooking yield, moisture content, fat retention and moisture retention values increased significantly ( p  < .05) in treatments. All mineral and textural parameters decreased significantly ( p  < .05) except manganese content. Lightness ( L *) values increased significantly ( p  < .05) with no significant effect on yellowness ( b *) and redness ( a *) values. All sensory scores decreased significantly ( p  < .05) except saltiness scores with incorporation of lemon albedo, however there was no significant difference in overall acceptability scores between control and 1% lemon albedo powder. It was concluded that lemon albedo at 1.0% level could be used as an effective fat replacer for development of ultra‐low‐fat chicken patties. Practical applications: Chicken patty exhibits industrial and economic importance, which is mainly affected by the raw material quality and composition. Patties containing less than 20 g/100 g fat content usually exhibit rubbery texture therefore, higher fat content is necessary to prepare patty without affecting its quality, however product with high fat content may exerts harmful effect on the human health such as obesity and high blood cholesterol levels. Citrus albedo is main by‐product of citrus industry which has great potential to be used as fat replacer in meat products along with various antioxidant, medicinal and functional properties. Incorporation of lemon albedo as fat replacer may enhance product's nutritional quality as well as functional properties.